2018
DOI: 10.1371/journal.pone.0191771
|View full text |Cite
|
Sign up to set email alerts
|

Association of usual sleep quality and glycemic control in type 2 diabetes in Japanese: A cross sectional study. Sleep and Food Registry in Kanagawa (SOREKA)

Abstract: ObjectivesExcessively short and long sleep durations are associated with type 2 diabetes, but there is limited information about the association between sleep quality and diabetes. Accordingly, the present study was performed to investigate this relationship.Materials and methodsThe subjects were 3249 patients with type 2 diabetes aged 20 years or older. Sleep quality was assessed by using the Pittsburgh Sleep Quality Index (PSQI). A higher global PSQI score indicates worse sleep quality, and a global PSQI sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
4
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 53 publications
7
36
4
8
Order By: Relevance
“…It revealed that 66.4% people with T2D suffer from sleep symptoms and that their QoL, including HRQoL and overall activity impairment, was worse than those of respondents without symptoms. This finding correlates with the results of previous studies [6][7][8][9][10]27]. Also, this study revealed that waking up to go to the bathroom and daytime sleepiness are associated with worse QoL in people with T2D.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It revealed that 66.4% people with T2D suffer from sleep symptoms and that their QoL, including HRQoL and overall activity impairment, was worse than those of respondents without symptoms. This finding correlates with the results of previous studies [6][7][8][9][10]27]. Also, this study revealed that waking up to go to the bathroom and daytime sleepiness are associated with worse QoL in people with T2D.…”
Section: Discussionsupporting
confidence: 92%
“…According to an internet survey of over 7 thousands people in the United States with T2D, three-quarters of participants suffered from sleep symptoms, and onequarter of them were actually diagnosed with a sleep disorder [6]. Also, reports show that about half of people with T2D in Japan have sleep disorder [7]. Furthermore, in a study of almost 1 thousand Chinese people with T2D, 33.6% suffered from poor sleep quality, and there was an association between the pittsburgh sleep quality index and QoL [8].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive long and short duration of sleep is associated with type 2 diabetes, as we have seen it from numerous epidemiological studies. A recent study from Japan investigated the link between sleep quality and diabetes among 3249 diabetic patients (<20 years) using the Pittsburgh Sleep Quality Index (PSQI); these patients were found to have poor subjective sleep quality due to increased sleep latency and a shorter duration of sleep [95]. The short duration of sleep is associated with increased incidence of T2DM as well as poor metabolic control in both type 1 and type 2 DM [26].…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative studies included 74,887 participants with mean age ranged from 42.2 to 66.0 years. These studies were conducted in China (n = 5), [20][21][22][23][24] Japan (n = 4), [25][26][27][28] South Korea (n = 2) 29,30 Taiwan (n = 2) 31,32 and one each in India, 33 Iran, 34 Thailand, 35 Turkey, 36 Singapore, 37 UAE. 38 The mean HbA1c levels, BMI (kg/m2), and FPG (mg/dL) were ranged from 7.0 to 8.52%, 23.8 to 29.5, and 108.77 to 168.00 respectively.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%